APLICAÇÃO DE DOSES DE GLIFOSATO EM DIFERENTES ESTÁDIOS FENOLÓGICOS DA CULTURA DA SOJA - PAULINO, Luiz Loesia Gomes; ANDRADE, Dener Coelho; OLIVEIRA, Luiz Anderson Abdalla; PEDROSO, Érico Carlos; ROSSI, Ana Carolina Marinho; SILVA, Matheus Gustavo (ANAIS DO ENIC, 2020)
-